Environmentally friendly turbo jet aerator for sustainable multitrophic aquaculture. Issue 1 (May 2021) - Tuwo, A; Yasir, I; Tresnati, J; Aprianto, R
Abstract: Aquaculture is an oxygen-dependent business; heterotroph biomass production is proportional to the oxygen supply to the aquaculture pond, therefore, intensive and supra-intensive aquaculture requires a large supply of oxygen. The use of paddle wheel aerators and the types of aerators available in the market today are generally wasteful in terms of energy use. This poster presents the test results of the Prototype Turbo Jet Aerator, which is named RA-TJA-SG1. This submersible aerator prototype was designed to be able to produce large amounts of oxygen with a small energy consumption (40 watts) using sustainable solar energy. Laboratory test results indicated that the RA-TJA-SG1 is able to increase the content of the concentration of dissolve oxygen in seawater at different salinity to the ideal concentration for intensive and supra intensive shrimp culture.